Pengaruh Kualitas Produk Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Listrik Prabayar (Studi Kasus Pada PT PLN (Persero) UIWS2JB Up3 Ogan Ilir ULP Indralaya) - Tutik Pebrianti; Zein Ghozali; Arubina Bangsawan; Hilwa Anggraini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
Product quality and service quality are factors that can provide customer satisfaction. The purpose of this study is to determine the effect of product quality and service quality on customer satisfaction. Product quality in this research was measured based on features, quality of work, durability, reliability, and conformance to specifications. Meanwhile, service quality was measured based on information quality, security & privacy, customer service & technical support. The questionnaire was distributed to 100 respondents, the prepaid electricity customers. The sample used in this study was simple random sampling. This study resulted variables of product and service quality both partially and simultaneously have a positive and significant effect on customer satisfaction.